Two siblings with fulminant viral hepatitis A: case report. - Yalniz, Mehmet; Ataseven, Hüseyin; Celebi, Selman; Poyrazoglu, Orhan Kürşat; Sirma, Nusret; Bahçeitoglu, Ibrahim Halil (My University, 2005)
Fulminant hepatitis is a rare complication of acute hepatitis A infection. Nevertheless, the seroepidemiology of the infection is rapidly changing with the developing world, rendering more adults susceptible to the infection, in particular with more severe course. We report here fulminant hepatitis A infection with a mortal course during an epidemic period in two siblings. Although it causes a self-limited mild disease, hepatitis A virus may have a severe course including fulminant hepatitis and may lead to mortality, especially in older ages. Hence, the risk of hepatitis A virus infection and its complications should be reduced with measures of immunization and sanitation.
Keywords: Acute Disease; Adolescent; Child; Family Health; Fatal Outcome; Female; Hepatitis A; Humans; Male; Siblings; acute disease; adolescent; article; case report; child; disease transmission; family health; fatality; female; hepatitis A; human; male; sibling